Kay ganda ng ating musika [videorecording] - Ledesma, Kuh (The Center, 1988)
Features our original Pilipino music song by Kuh Ledesma, interview with Bill Beyer about the Banaue Rice Terraces and rituals about rice harvest; F. Landa Jocano on Tagbanuas' ceremony; Lucrecia Kasilag on the ethnic musical instruments of Mindanao; Felipe de Leon on romanticism and Gerry Hingco on the T'boli.